2024
DOI: 10.3389/fphar.2023.1327185
|View full text |Cite
|
Sign up to set email alerts
|

PCSK-9 inhibitors: a new direction for the future treatment of ischemic stroke

Lin Zhou,
Hongyu Zhang,
Shuyi Wang
et al.

Abstract: Ischemic stroke, the most prevalent and serious manifestation of cerebrovascular disease, is the main cause of neurological problems that require hospitalization, resulting in disability and death worldwide. Currently, clinical practice focuses on the effective management of blood lipids as a crucial approach to preventing and treating ischemic stroke. In recent years, a great breakthrough in ischemic stroke treatment has been witnessed with the emergence and use of a novel lipid-lowering medication, Proprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…For example, Ya-Wen Lu et al performed a single-center retrospective study, recruiting 409 patients with acute myocardial infarction, to explore the relationships between baseline LDL-C concentrations and clinical outcomes according to different nutritional status, and the results showed that lipid paradox was only observed among patients at high-risk of malnutrition 42 . All those results hints that although current clinical practice concentrates on the lipid-lowering therapy and effective control of serum lipids as a crucial approach to preventing or treating ischemic stroke 43,44 , when treating patients with malnutrition, the improvement of nutritional status may be more beneficial than strict lipid management.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ya-Wen Lu et al performed a single-center retrospective study, recruiting 409 patients with acute myocardial infarction, to explore the relationships between baseline LDL-C concentrations and clinical outcomes according to different nutritional status, and the results showed that lipid paradox was only observed among patients at high-risk of malnutrition 42 . All those results hints that although current clinical practice concentrates on the lipid-lowering therapy and effective control of serum lipids as a crucial approach to preventing or treating ischemic stroke 43,44 , when treating patients with malnutrition, the improvement of nutritional status may be more beneficial than strict lipid management.…”
Section: Discussionmentioning
confidence: 99%